The Agononida incerta species complex unravelled (Crustacea: Decapoda: Anomura: Munididae) - Poore, Gary C. B.; Andreakis, Nikos (Zootaxa, 2012)
Squat lobsters from Australia, east Africa, Taiwan, Philippines and the Norfolk Ridge (southwestern Pacific) previouslyidentified as Agononida incerta (Henderson, 1888) are redescribed as four new species in addition to the original: A.africerta, A. auscerta, A. indocerta and A. norfocerta. A. rubrizonata Macpherson & Baba, 2009, also earlier confusedwith this species, is redescribed. All six species are morphologically distinguishable only on the basis of the shape of theanterolateral lobe of the telson and the shape and setation of the dactyli of pereopods 2–4. The morphological delineationof these species and their taxonomic status are robustly supported by phylogenetic analysis of the partial mitochondrialCOI marker. Taken together, subtle morphological differences, geographical distribution patterns and genetic discontinuities have important implications for understanding diversity, systematics and evolution of squat lobsters.